Controlled Chaos Based on Tellegen's Principle in Electric Power Systems - Basic Approach. Issue 27 (2016) - Stork, M.; Mayer, D.; Hrusak, J.
Abstract: The paper deals with a new problem of physical correctness detection in the area of strictly causal system representations. The proposed approach to the problem solution is based on generalization of Tellegen's theorem well known from electrical engineering. The novelty of this approach is that it is based on the abstract state space energy for real linear, nonlinear and chaotic systems e.g. electrical circuits and power lines with distributed parameters. Consequently, mathematically as well as physically correct results are obtained. Some known and often used system representation structures are discussed from the developed point of view as an addition. The examples are also included.